2019
DOI: 10.1016/j.hjdsi.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of two triggered palliative care consultation approaches on consult implementation in oncology

Abstract: Across two inpatient oncology services, TPCC supported by multiple strategies had the greatest impact on uptake. How strategies affect sustained use of palliative care consults remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Despite medical oncology clinicians’ lack of awareness, there was a strong upward spike in consult uptake after the initiation of the formal implementation policies and practices in October 2015. Indeed, Figure 3 is illustrative of a significant increase previously reported in a study by the authors which used a difference-in-differences analysis to compare uptake before and after palliative care consult implementation in the oncology services (DiMartino et al, In Press). This disparate finding is surprising and may be attributed to when implementation climate was assessed.…”
Section: Discussionmentioning
confidence: 76%
“…Despite medical oncology clinicians’ lack of awareness, there was a strong upward spike in consult uptake after the initiation of the formal implementation policies and practices in October 2015. Indeed, Figure 3 is illustrative of a significant increase previously reported in a study by the authors which used a difference-in-differences analysis to compare uptake before and after palliative care consult implementation in the oncology services (DiMartino et al, In Press). This disparate finding is surprising and may be attributed to when implementation climate was assessed.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, and others ( 45 ) we have sought through exploring triggers to test a universal approach to identifying the group of people who may benefit from palliative care. A handful of other single-centre studies have similarly examined models of ‘triggered palliative care consultation’, often also initiated on criteria involving hospitalisation, and these have reported variable outcomes ( 26 , 27 , 29 ). Adelson and colleagues used a hybrid of automatic criteria relating to health service use (prior hospital within 30 days; or > 7 bed days) and active symptoms for prompting palliative care referral, resulting in a two-fold increase in rates of consultation and a significant reduction of hospital re-admission ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rocque and colleagues demonstrated improved illness understanding following implementation of triggered palliative care for all hospitalised cancer patients with metastases, but this resulted in a minimal impact upon patient-reported symptoms, hospice utilisation, and cost of care ( 29 ). DiMartino and colleagues reported triggered palliative care for hospitalized solid tumour and gynecologic patients increased uptake, but this did not result in earlier timing of consultations ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that improvement in the implementation for referral for PC consultation in patients screening positive is necessary. TPCC DiMartino et al (31) studied the use of TPCC in gynecologic cancer patients admitted to the hospital. For this study, a single strategy consisting of a printed guideline to prompt PC referral was placed in a patient's chart.…”
Section: Clinical Triggersmentioning
confidence: 99%